N-benzyl-N-methyldecan-1-amine, derived from garlic, and its derivative alleviate 2,4-dinitrochlorobenzene-induced atopic dermatitis-like skin lesions in mice - Ji Eun Kim; Phatcharaporn Budluang; Jumin Park; Kon Ho Lee; Sirichatnach Pakdeepromma; Chutima Kaewpiboon; Ho Young Kang; Dae Youn Hwang; Young-Hwa Chung (My University, 2024)
Given the intricate etiology and pathogenesis of atopic dermatitis (AD), the complete cure of AD remains challenging. This study aimed to investigate if topically applying N-benzyl-N-methyldecan-1-amine (BMDA), derived from garlic, and its derivative [decyl-(4-methoxy-benzyl)-methyl-1-amine] (DMMA) could effectively alleviate AD-like skin lesions in 2,4-dinitrochlorobenzene (DNCB)-treated mice. Administering these compounds to the irritated skin of DNCB-treated mice significantly reduced swelling, rash, and excoriation severity, alongside a corresponding decrease in inflamed epidermis and dermis. Moreover, they inhibited spleen and lymph node enlargement and showed fewer infiltrated mast cells in the epidermis and dermis through toluidine-blue staining. Additionally, they led to a lower IgE titer in mouse sera as determined by ELISA, compared to vehicle treatment. Analyzing skin tissue from the mice revealed decreased transcript levels of inflammatory cytokines (TNF-α, IL-1β, and IL-6), IL-4, iNOS, and COX-2, compared to control mice. Simultaneously, the compounds impeded the activation of inflammation-related signaling molecules such as JNK, p38 MAPK, and NF-κB in the mouse skin. In summary, these findings suggest that BMDA and DMMA hold the potential to be developed as a novel treatment for healing inflammatory AD.
Keywords: Pathogenesis; Epidermis (zoology); Hairless; Dermatology and Skin Diseases